Evidence Cafés: Overcoming conflicting motivations and timings. (22nd September 2020) - Clough, Gill; Adams, Anne
Abstract : page_220 other Evidence-based practice is increasingly important in creating effective public services through the balance of high-quality research and valid practice. Yet even when academics and practitioners work together to use evidence in practice, barriers emerge. This paper describes research into equitable knowledge exchange between academia and practice, drawing on data from 15 Evidence Cafés run across the UK with police forces, involving 378 participants, represented here with three exemplar Evidence Café case studies. Our findings reveal the differences between one-way knowledge transfer and two-way, equitable knowledge exchange, and how champions and effectively designed and implemented discussion objects can overcome challenges of conflicting motivations and timing. We conclude that there is a need to reframe knowledge exchange through the lens of 'evidence' and the process of equitable co-creation of new meanings.